Hubungan Status Gizi dan Kejadian Anemia dengan Kesegaran Jasmani pada Remaja Putri Kelas X dan XI di SMA Muhammadiyah 1 Surakarta - Iryanti, Ninda Puji; , Rustiningsih, SKM., M.Kes; , Wahyuni, S.Fis., M.Kes (2015)
Introduction : Physical fitness is an indicator of health, which is important for the adolescents because it predicts health effects and is related to the increase of health level. Adolescent girls have lower physical fitness than boys. Furthemore, there are many determinants of physical fitness, including nutrition status and haemoglobin level. Objective : The purpose of this research was to assess the correlations between nutrition status, status of anemia and physical fitness in adolescent girls of class X and XI at Muhammadiyah High School 1 of Surakarta. Research Method : This research used observational with cross-sectional design. The respondens were choosen through simple random sampling from X and XI graders who fullfilled the inclusion criteria and there were 40 respondens in total. Nutrition status was obtained through Body Mass Indeks (BMI). The status of anemia was obtained using Cyanmethemoglobin method and physical fitness was obtained using Harvard Step Test method. Result : There was a correlation between nutrition status and physical fitness at Muhammadiyah High School 1 of Surakarta (p=0,040), and No correlation was found between the status of anemia and physical fitness in adolescent girls of Muhammadiyah High School 1 of Surakarta (p=0,505). Conclusion : There was a correlation between nutrition status and physical fitness but no correlation between status of anemia and physical fitness in adolescent girls at Muhammadiyah High School 1 of Surakarta.